Mandible Movements in Japanese : A Comparative Study with Mandarin Speakers - Wang, Kexin; Chen, Kaiqiao; Sun, Jing; Frid, Johan ; 0000-0003-4704-5559; Hayashi, Ryoko; Erickson, Donna; Niebuhr, Oliver (188th Meeting of the Acoustical Society of America joint with 25th International Congress on Acoustics, 2025-05-18, 2025)
This study analyzed Japanese mandible movements using a recently developed technique, the MARRYS helmet [Gudmundsson et al., Interspeech (2024)]. Data were collected from 9 first language and 10 second language (Mandarin Chinese) speakers of Japanese. The speech materials included three sentences composed entirely of /a/ vowels, one neutral sentence and three focus sentences with emphasis on different target words. The results revealed that Japanese speakers showed greater variations in the jaw movements compared to Mandarin speakers. For native speakers, we observed that the right boundaries of phonological phrases and utterances were often accompanied by an increased mandible lowering, while the tendency was not noticeable for Mandarin speakers. On the other hand, at the right boundary of prosodic words, the mandible lowering was not pronounced for either Japanese speakers or Mandarin speakers. Moreover, the mora carrying the accent pitch nucleus was not often accompanied by the increased mandible lowering for both groups. For the focus sentences, native Japanese speakers showed more increased mandible lowering for emphasized words than Mandarin speakers. The findings indicate that there still remain challenges in acquiring articulatory and prosodic features for Japanese learners.